Does high investment lead to high efficiency in Chinese Super League clubs?. Issue 4 (23rd February 2023) - Fan, Mu; Liu, Fei; Yi, Qing; Gong, Bo
ABSTRACT: The cost of operating Chinese football clubs has increased, prompting the need to examine their operating efficiency. Hence, this study proposes an integrated approach to analyse the efficiency of Chinese Super League (CSL) football clubs from 2014 to 2019. We used data envelopment analysis (DEA) model with three dimensions of output indicators and a bootstrap DEA model to find that CSL clubs, particularly high-input clubs, have low efficiency. These results are robust to other alternative estimation methods. Further research revealed that the scale of CSL club inputs is negatively correlated with operating efficiency, with low scale efficiency acting as a major impediment to the growth of CSL clubs. The comprehensive evaluation model proposed in this study provides an in-depth analysis of the overall efficiency of football clubs and helps managers evaluate and provide feedback based on the realities of the market.